Anti‐tumoral effects of exercise on hepatocellular carcinoma growth. Issue 5 (22nd March 2018) - Saran, Uttara; Guarino, Maria; Rodríguez, Sarai; Simillion, Cedric; Montani, Matteo; Foti, Michelangelo; Humar, Bostjan; St‐Pierre, Marie V.; Dufour, Jean‐François
Abstract : Regular physical exercise has many beneficial effects, including antitumor properties, and is associated with a reduced risk of developing hepatocellular carcinoma (HCC). Less is known about the impact of exercise on HCC growth and progression. Here, we investigated the effects of exercise on HCC progression and assessed whether any beneficial effects would be evident under sorafenib treatment and could be mimicked by metformin. American Cancer Institute rats with orthotopic syngeneic HCC derived from Morris Hepatoma‐3924A cells were randomly assigned to exercise (Exe) and sedentary groups, or sorafenib±Exe groups or sorafenib±metformin groups. The Exe groups ran on a motorized treadmill for 60 minutes/day, 5 days/week for 4 weeks. Tumor viable area was decreased by exercise, while cell proliferation and vascular density were reduced. Exercise increased the expression of phosphatase and tensin homolog deleted from chromosome 10 and increased the phosphorylation of adenosine monophosphate‐activated protein kinase, while the phosphorylation of protein kinase B, S6 ribosomal protein, and signal transducer and activator of transcription 3 were decreased. Transcriptomic analysis suggested major effects of exercise were on nontumoral liver rather than tumor tissue. Exercise demonstrated similar effects when combined with sorafenib. Moreover, similar effects were observed in the group treated with sorafenib+metformin, revealing an exercise‐mimicking effect of metformin. Conclusion: Exercise attenuates HCC progression associated with alterations in key signaling pathways, cellular proliferation, tumor vascularization, and necrosis. These beneficial effects are maintained when combined with sorafenib and can be mimicked by metformin. ( Hepatology Communications 2018;2:607‐620)